Persistence of experimental Rocio virus infection in the golden hamster (Mesocricetus auratus) - Daniele Freitas Henriques; Juarez Antonio Simões Quaresma; Helen Thais Fuzii; Márcio Roberto Teixeira Nunes; Eliana Vieira Pinto da Silva; Valéria Lima Carvalho; Lívia Carício Martins; Samir Mansour Moraes Casseb; Jannifer Oliveira Chiang; Pedro Fernando da Costa Vasconcelos (Memorias do Instituto Oswaldo Cruz, 2012)
Rocio virus (ROCV) is an encephalitic flavivirus endemic to Brazil. Experimental flavivirus infections have previously demonstrated a persistent infection and, in this study, we investigated the persistence of ROCV infection in golden hamsters (Mesocricetus auratus). The hamsters were infected intraperitoneally with 9.8 LD50/0.02 mL of ROCV and later anaesthetised and sacrificed at various time points over a 120-day period to collect of blood, urine and organ samples. The viral titres were quantified by real-time-polymerase chain reaction (qRT-PCR). The specimens were used to infect Vero cells and ROCV antigens in the cells were detected by immunefluorescence assay. The levels of antibodies were determined by the haemagglutination inhibition technique. A histopathological examination was performed on the tissues by staining with haematoxylin-eosin and detecting viral antigens by immunohistochemistry (IHC). ROCV induced a strong immune response and was pathogenic in hamsters through neuroinvasion. ROCV was recovered from Vero cells exposed to samples from the viscera, brain, blood, serum and urine and was detected by qRT-PCR in the brain, liver and blood for three months after infection. ROCV induced histopathological changes and the expression of viral antigens, which were detected by IHC in the liver, kidney, lung and brain up to four months after infection. These findings show that ROCV is pathogenic to golden hamsters and has the capacity to cause persistent infection in animals after intraperitoneal infection.